Importance of electroconvulsive treatment: letters to the editor regarding the article the diagnosis and treatment of unipolar depression - Zilles-Wegner, David; Sartorius, Alexander (Deutsches Ärzteblatt, 2024)
As Härter and Prien in their article focused on the innovations in the guideline, the importance of electroconvulsive therapy (ECT) was not adequately discussed, in our opinion. The text mentions ECT merely as a “may be considered”...
Gesehen am 18.03.2025